Synchronous online discussion : its contributions to language learning - Abdul Ghani, Rozina; Mat Daud, Nuraihan (Karisma Publications Sdn Bhd., 2008)
Many institutions are opting for web-based teaching and learning. some courses are offered online to serve a bigger $oup of students. This includes the teaching of second and foreign languages. various steps have been taken to integrate the technology in teaching. The intemet facilities may be manipulated to encourage students to interact in the target language. The textual nature of such communication allows users to look at students' language usage. The constraints imposed by the technology and students' limited knowledge of the language may, however, influence the quality of language production. This chapter exarnines the potential of the chat facilities as a means of classroom communication. The study focuses on the computermediatede xchangesa mong intermediateE SL/EFLs tudentso f the Intemational Islamic University Malaysia